A new species of Allecula (Coleoptera: Tenebrionidae: Alleculinae) from cork oak stands of Italy - Novák, Vladimír; Jansson, Nicklas; Chiari, Stefano; Zauli, Agnese; Audisio, Paolo; Carpaneto, Giuseppe M. (Zootaxa, 2012)
A new species of comb-clawed beetle, Allecula suberina Novák sp. nov., is described, illustrated and compared with all western Palaearctic species. The new species is probably saproxylic, as are other species in the genus, because all specimens were collected by traps set within or near tree cavities on old hollow cork oaks (Quercus suber).